2015
DOI: 10.1111/plb.12396
|View full text |Cite
|
Sign up to set email alerts
|

Temperature determines size and direction of effects of elevated CO2 and nitrogen form on yield quantity and quality of Chinese cabbage

Abstract: Rising atmospheric CO2 concentrations (e[CO2 ]) are presumed to have a significant impact on plant growth and yield and also on mineral nutrient composition, and therefore, on nutritional quality of crops and vegetables. To assess the relevance of these effects in future agroecosystems it is important to understand how e[CO2 ] interacts with other environmental factors. In the present study, we examined the interactive effects of e[CO2 ] with temperature and the form in which nitrogen is supplied (nitrate or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 88 publications
(164 reference statements)
0
11
0
Order By: Relevance
“…Interestingly, N form also interacts with eCO 2 and hence affects the product quality of Chinese cabbage ( Reich et al, 2016 ) and sweet pepper ( Piñero et al, 2017b ). Specifically, eCO 2 (800 vs. 420 μmol mol -1 ) increased P concentration and maintained S concentration in shoots of 20-day-old Chinese cabbage in 1.88 mM NH 4 NO 3 at a temperature of 15/12°C (day/night), while it maintained P concentration and decreased S concentration in plants supplied with 3.75 mM NO 3 - ( Reich et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, N form also interacts with eCO 2 and hence affects the product quality of Chinese cabbage ( Reich et al, 2016 ) and sweet pepper ( Piñero et al, 2017b ). Specifically, eCO 2 (800 vs. 420 μmol mol -1 ) increased P concentration and maintained S concentration in shoots of 20-day-old Chinese cabbage in 1.88 mM NH 4 NO 3 at a temperature of 15/12°C (day/night), while it maintained P concentration and decreased S concentration in plants supplied with 3.75 mM NO 3 - ( Reich et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…One possible explanation for this observation is a change in rhizosphere pH. It is well-known that zinc uptake negatively correlates with rhizosphere pH (Lucas and Davis, 1961 ; Marschner, 1993 ), which is the likely reason for higher zinc uptake under ammonium nutrition and phosphorus deficiency which both lead to an acidification of the rhizosphere (Alloway, 2009 ; Reich et al, 2016 ). Measurements with H + -electrodes showed that sulfur deficiency also leads to a lower pH at the roots of B. pekinensis seedlings (Reich et al, 2014b ), which could increase zinc uptake.…”
Section: Resultsmentioning
confidence: 99%
“…In soybean leaves, ureide (derived from urea) and total amino acid levels were increased at the early season, but, later it resumed to initial level ( Rogers et al, 2006 ). Similarly, a combination of temperature and elevated CO 2 efficiently decreases the levels of amino acids in root of Chinese cabbage ( Reich et al, 2016 ). In the strawberry fruit, elevated CO 2 and high temperature increase the sugar and sweetness index along with a reduction in the antioxidant and nitrogen content ( Sun et al, 2012b ).…”
Section: Impact Of High Co 2 Stress On the Metabolmentioning
confidence: 99%